Estudio serológico e inmunológico de dos nuevas variantes del virus aftoso tipo A de Colombia. - Turriago, Gustavo; Morales, A.; Lobo Arias, César; Jaramillo G, M. (Instituto Zooprofiláctico Colombiano, 2018)
Salud animal